2015
DOI: 10.3171/2014.11.jns1449
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy to treat newly diagnosed solitary brain metastasis: initial experience and long-term outcomes

Abstract: abbreviatioNs BrM = brain metastasis; GPA = Graded Prognostic Assessment; IORT = intraoperative radiotherapy; KPS = Karnofsky Performance Scale; LMD = leptomeningeal (metastatic) disease; NSCLCa = non-small cell lung cancer; RPA = recursive partitioning analysis; SRS = stereotactic radiosurgery; WBRT = whole-brain radiation therapy; XRS = radiation source. submitted January 30, 2014. accepted November 13, 2014. iNclude wheN citiNg Published online January 23, 2015; DOI: 10.3171/2014.11.JNS1449. disclosure The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 49 publications
(120 reference statements)
1
41
2
1
Order By: Relevance
“…Traditionally, the standard of care for patients with solitary brain metastasis has been resection plus whole-brain radiotherapy (WBRT) [4, 7]. Resection allows for histopathological examination of the tissue and has been shown to improve neurological symptoms, functional independence, and survival [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the standard of care for patients with solitary brain metastasis has been resection plus whole-brain radiotherapy (WBRT) [4, 7]. Resection allows for histopathological examination of the tissue and has been shown to improve neurological symptoms, functional independence, and survival [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given that patients with systemic cancer are now living longer due to improved extracranial anti-tumor strategies, concerns related to these delayed, radiation-induced neurotoxic effects are prompting neuro-oncologists to assess alternatives to WBRT [4, 14]. Many centers are therefore using targeted techniques with limited radiation exposure, such as stereotactic radiosurgery (SRS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IORT was also used to safely treat locally advanced and recurrent rectal cancer, producing effects similar other intraoperative radiotherapy techniques but with a shorter operative time [6]. In addition, Weil et al [7] reported the feasibility of using IORT to treat brain metastases, and Wenz et al [22] reportedly used IORT to treat advanced thoracic spinal metastases, with good results. Finally, Rutkowski et al [9] reported the feasibility using IORT to treat early oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results are comparable to other current treatment paradigms. 43 Local therapy with intraoperative radiation or brachytherapy may be a particularly attractive option for lesions that result in resection cavities too large to be treated safely with SRS such as those great than 15 ml in volume. 44,45 Local radiation to the resection cavity, either via SRS or intraoperative radiotherapy, has been associated with an increased rate of distant failure and leptomeningeal disease in comparison to adjuvant WBRT.…”
Section: Radiosurgery To the Resection Cavitymentioning
confidence: 99%